Pedagogy of resistance: the denial as a key element of (de)formation (Praxis Educativa, 2018)
In this article, the authors propose a reflection on the idea of negativity in  a critical and philosophical perspective that can approach in other ways the meanings and purposes of the formation of both the individual and the thought in current times. The denial, or yet, a philosophy of negativity (Adorno, 2009) is presented as a breeding ground for a reconfiguration of the pedagogical ideal and its possibilities to question the anthropological and historical features of what is introduced to us as the truth. The attitude of resistance is, in this text, a key component to the possibility of this philosophy of negativity, which allows us to expand our horizon of thinking and action. The actual intent couldn’t be further from an irrefutable conclusion, quite the contrary. We intend to inspire a provocative debate that destabilizes both the idea of the selfconscious individual and of how they relate with the world. We understand that this is a way to open possibilities to other experiences and narratives about the process of formation and (de)formation in the education.
Keywords: Theodor Adorno; resistance; negativity